IMPLEMENTASI MODEL PEMBELAJARAN PAI ONLINE BERBASIS LEARNING MANAGEMENT SYSTEM - Amrini Shofiyani; Maydatul Akmalyah Machfud; Moh Yasin Fatchul Barry (Jurnal Education and Development, 2023)
Learning Management System in general is a software specifically designed to distribute, create, and manage learning content. This condition inspired researchers to conduct research with the aim of implementing the Learning Management System-Based Online PAI Learning Model (Case Study of Kabuh High School in Mangunan Village, Kabuh District, Jombang Regency). The objectives to be achieved in this study are to: 1) Know the implementation of the Learning management system-based online PAI learning model at Kabuh High School in Mangunan Village, Kabuh sub-district, Jombang Regency. 2) find out the results in implementing the implementation of online learning models based on learning management systems. This research is qualitative in nature, data obtained from field observations, interviews, and documentation from school archive data and analyzed using descriptive methods. The results of the research findings show that using applications and educational platforms which of course can be used to support teaching and learning activities, for example: Google classroom, and Watshapp which are made in order to be able to implement learning models.